Glycine–Nitrate Process for the Elaboration of Eu3+‐Doped Gd2O3 Bimodal Nanoparticles for Biomedical Applications. Issue 7 (18th November 2014) - Goglio, Graziella; Kaur, Gaganpreet; Pinho, Sonia L. C.; Penin, Nicolas; Blandino, Alexia; Geraldes, Carlos F. G. C.; Garcia, Alain; Delville, Marie‐Helene
Abstract: Monoclinic and cubic europium‐doped Gd2 O3 structures were selectively synthesized by the glycine–nitrate process by fine control of the synthesis temperature through the crucial fuel/oxidant ratio. The cubic phase is obtained under fuel‐rich conditions, whereas stoichiometric conditions induce the simultaneous formation of cubic and monoclinic polymorphs. The samples were subjected to appropriate sintering to obtain highly crystalline and carbon‐free materials. The average nanoparticle (NP) size determined by TEM for these nanopowders (23 nm) agrees with the average crystallite sizes obtained from XRD Rietveld analysis; therefore, the particles are monocrystalline. Both electron energy loss spectroscopy (EELS) and photoluminescence studies showed that the europium‐doped NPs are highly luminescent, and the Eu 3+ ions are homogeneously distributed over the whole material as well as over the two gadolinium crystallographic sites of the cubic phase. These fluorescent NPs exhibit relaxivities that define them as potential T1 contrast agents for further biomedical applications. Abstract : By fine control of the flame temperature in the glycine–nitrate process, highly crystalline Eu 3+ ‐doped and undoped Gd2 O3 nanoparticles are obtained. In the doped samples, the Eu 3+ ions are homogeneously distributed over the whole material. The Eu:Gd2 O3 NPs are highly luminescent and exhibit relaxivities that define them as potential T1 contrast agents for biomedical applications.